Scripts : elegant lettering from design's golden age - Heller, Steven, 1939-1997; Fili, Louise, 1951- (London : Thames & Hudson, 2011)
"Seen in everything from wedding invitations and birth announcements to advertisements, menus, street signs, and diplomas, script typefaces impart elegance and sophistication to a broad variety of texts. Scripts never go out of style, and the hundreds of inventive examples here, many found in obscure sources from across Europe and America, are sure to inspire today's designers"--Back cover.
Introduction -- French : scriptes -- British : scripts -- German : der Schrift -- Italian : il corsivo -- American : scripts -- Further reading.
Keywords: Alphabet books; Calligraphy; Lettering; Typographie